Endocrine stress responses and risk of type 2 diabetes mellitus. (3rd September 2015) - Siddiqui, Azaz; Madhu, S. V.; Sharma, S. B.; Desai, N. G.
Abstract: This study was carried to ascertain whether stress responses are associated with abnormalities in glucose tolerance, insulin sensitivity and pancreatic beta cell function and risk of type 2 Diabetes Mellitus. Salivary cortisol, a marker of hypothalamic-pituitary-adrenal (HPA) axis and salivary α-amylase, a marker of sympathetic nervous system (SNS) were compared in 125 subjects of newly detected diabetes mellitus (NDDM) and normal glucose tolerance (NGT) subjects who were diagnosed on the basis of oral glucose tolerance test (OGTT). Assessment of stress in them was done through stress scales – presumptive stressful life events scale (PSLES), perceived stress scale (PSS) and sense of coherence (SOC) and correlated with these and other stress response markers. Significantly higher 10 pm salivary cortisol and post dexamethasone salivary cortisol were found in NDDM subjects as compared to NGT. 10 pm salivary cortisol correlated significantly with fasting plasma glucose (FPG), 2 h plasma glucose (2h PG) and glycated hemoglobin (HbA1c) while post dex salivary cortisol correlated with 2h PG, HbA1c and salivary α-amylase with 2h PG. Stepwise logistic regression analysis showed that body mass index (OR: 1.840), SOC (OR: 0.688) and 10 pm salivary cortisol (OR: 1.427) were the strongest predictors of NDDM. The results of the present study indicate that NDDM subjects display significantly higher chronic stress and stress responses when compared to subjects with NGT. Chronic stress and endocrine stress responses are significantly associated with glucose intolerance, insulin resistance and diabetes mellitus.